2013
DOI: 10.1002/ajmg.a.36149
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine phenotype of 6q16.1–q21 deletion involving SIM1 and Prader–Willi syndrome‐like features

Abstract: Proximal interstitial 6q deletion involving Single-minded 1 (SIM1) gene causes a syndromic form of obesity mimicking Prader-Willi syndrome. In addition to obesity, Prader-Willi syndrome includes several other endocrinopathies, such as hypothyroidism, growth hormone deficiency, and hypogonadotropic hypogonadism. The endocrine phenotype of interstitial 6q deletion remains largely unknown, although clinical similarities between Prader-Willi syndrome and interstitial 6q deletion suggest endocrine abnormalities als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 28 publications
(44 reference statements)
1
32
0
Order By: Relevance
“…If two or more articles reported the same chromosomal alterations for PW-like phenotype, the most recent was chosen. Twelve articles of 14 were case reports (Lukusa and Fryns, 2000;De Molfetta et al, 2002;Florez et al, 2003;Stalker et al, 2003;Niyazov et al, 2007;Nowicki et al, 2007;Gabbett et al, 2008;Pramyothin et al, 2010;Tsuyusaki et al, 2010;Ben-AbdallahBouhjar et al, 2012;Doco-Fenzy et al, 2013;Izumi et al, 2013) and two reported series of cases: one of 78 cases (Hosoki et al, 2009) and another of 9 cases (D'Angelo et al, 2013) ( Table 1). The patients included in this review were clinically diagnosed as bearing the PWlike phenotype because they were negative for alterations on 15q11-q13.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If two or more articles reported the same chromosomal alterations for PW-like phenotype, the most recent was chosen. Twelve articles of 14 were case reports (Lukusa and Fryns, 2000;De Molfetta et al, 2002;Florez et al, 2003;Stalker et al, 2003;Niyazov et al, 2007;Nowicki et al, 2007;Gabbett et al, 2008;Pramyothin et al, 2010;Tsuyusaki et al, 2010;Ben-AbdallahBouhjar et al, 2012;Doco-Fenzy et al, 2013;Izumi et al, 2013) and two reported series of cases: one of 78 cases (Hosoki et al, 2009) and another of 9 cases (D'Angelo et al, 2013) ( Table 1). The patients included in this review were clinically diagnosed as bearing the PWlike phenotype because they were negative for alterations on 15q11-q13.…”
Section: Resultsmentioning
confidence: 99%
“…After the application of these techniques, the authors were able to exclude classical PWS, i.e., the syndrome caused by deficiency on 15q11-q13. They investigated further and discovered other mutations that could be associated with the PW-like phenotype, such as: a molecular pattern compatible with Angelman's syndrome (De Molfetta et al, 2002); chromosome 14 maternal uniparental disomy (Hosoki et al, 2009); monosomy of 1p36 (Tsuyusaki et al, 2010); deletion of 6q (Izume et al, 2013), 2pter deletion (Doco-Fenzy et al, 2013); and 10q26 deletion (Lukusa and Fryns, 2000); paracentric inversion (X)(q26q28) (Florez et al, 2003); 12q subtelomere deletions (Niyazov et al, 2007); Xq27-qter disomy; deletion 3p26.3 (Ben-Abdallah-Bouhjar et al, 2012); fragile X (Nowicki et al, 2007); and fragile X with 47,XYY (Stalker et al, 2003); deletion in 6q (Izumi et al, 2013); and Klinefelter syndrome karyotype, which showed a duplication of X(q21.1-q21.31) (Pramyothin et al, 2010) (Table 1). Recently, D'Angelo et al (2013) reported different copy number imbalances of chromosomes 2, 3, 6, 10, 12, 14, and X, in nine patients showing the PW-like phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3, However, few of them underwent molecular characterisation of their genetic abnormalities, using either chromosomal microarray analysis, 3,13,[15][16][17][18]22,23,25 fluorescence in situ hybridisation (FISH) analysis with bacterial artificial chromosomes (BAC) clones 21 or STR analysis. 24 Two publications evaluated genotype-phenotype correlations at the 6q16 locus, but included only five and three patients, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was suggested that deletions in SIM1 at 6q16.3 were responsible for Prader-Willi-like phenotypes [Izumi et al, 2013], while deletions in NR2E1 and SNX3 (and likely additional genes in the 6q21 region) would contribute to microcephaly [Kumar et al, 2007;Mizutani et al, 2009], and deletions of 6q21q22.31 were associated with the acro-cardio-facial syndrome phenotype [Toschi et al, 2012;Hudson et al, 2014].…”
Section: Discussionmentioning
confidence: 99%